MCK SEBAGAI PRORITAS UTAMA DALAM KESEHATAN KELUARGA - Fajar Hidayanto (UII, 2015)
MCK is a room where someone can shower to cleanse the body. Cleanlinessfamily centered MCK, makes MCK’s cleanliness is really important. MCK in poorhygiene system will invite many germs grow and eventually create risk of germs andliving environment becomes unhealthy. Observations by author at Dukuh Jati, DesaGerbosari, Kulon Progo, Yogyakarta found that there are still many people who do notcare about the cleanliness of its MCK. Therefore, the authors took the initiative toprovide education about healthy MCK. With hope, Dukuh Teak be concerned with thecleanliness of its toilets.